Jejak Tafsir Parateksual di Indonesia - Nor Lutfi Fais; Kun Khoiro Umam Al Muafa; Egi Tanadi Taufik (Lajnah Pentashihan Mushaf Al-Qur'an, 2025)
This article examines quotations of Al-Wahidiy’s and Al-Ijiy’s Qur’an interpolations in a Jalalain manuscript, located in the Museum of the Grand Masjid of Central Java. The presence of these interpolations reflects the tradition of peripheral Qur’an commentary. This research adapts the codicological and paratextual analysis to determine the paratextual interpolation of the two Qur’an commentaries, while identifying the manuscript culture of the Jalalayn manuscript in the past. Results suggest that each interpolation of Al-Wahidiy and Al-Ijiy is quoted in different circumstances within a distinctive pattern. The scribe did not act arbitrarily in presenting the paratexts, but instead involved the cognitive process of understanding and signifying the Qur’anic text. This instance is visible from the differences between the original text given by the original authors compared to the paratext of the scribe, e.g. additions and reductions. Nevertheless, the textual source used by the scribe is undetermined, considering the absence of historical data on the circulation of Al-Wahidiy’s and Al-Ijiy’s manuscripts in the past.